The Neotropical genera Oxycrepis Reiche and Stolonis Motschulsky: a taxonomic review, key to the described species and description of new Stolonis species from Ecuador (Coleoptera: Carabidae: Loxandrini) - Will, Kipling W. (Zootaxa, 2005)
Five species of Stolonis (Carabidae: Loxandrini) are newly described: S. yasuni Will, sp. n., S. spinosus Will, sp. n., S. catenarius Will, sp. n., S. tapiai Will, sp. n. from Yasuni Scientific Station, Orellana Province (previously part of Napo Province), Ecuador and S. scortensis Will, sp. n. with its type locality Reserva Faunistica Cuyabeno, Sucumbios Province, Ecuador. A key to adults of Stolonis and Oxycrepis species is provided. Generic concepts for these taxa are briefly reviewed.